Strategic Analysis on Start-Up Business Using Objectives and Key Results Method in Rumah Kapas Holding - Bassam Muhammad Drehem; Iwan Vanany (Institut Teknologi Sepuluh Nopember, 2020)
The Textile and Garment Industry is one of the industrial sectors in Indonesia which is a priority by the Ministry of Industry in the